PENGARUH PENGGANTIAN PASIR LUMAJANG DENGAN PASIR ERUPSI GUNUNG KELUD TERHADAP KUALITAS MORTAR - Nawir Rasidi; Diana Ningrum (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
Mortar serves to increase the resilience of the bond and the bond with a constituent part of this part of the construction. Mortar strength depends on the cohesion of the cement paste to aggregate the fine particles. This study use traditional testing methods for analyzing the compressive strength marshall mortar with a variation of 0%, 50% and 100%, the age of 7 days, 14 days, and 28 using the composition 1pc: 3PS, 1pc: 4Ps, and 1pc: 6ps. Making the test object to the composition of the test object 5 0% for sand Lumajang, 50% sand and Kelud Lumajang, and 100% sand Kelud. Implementation phases include testing of materials, namely water, cement, and sand. Pengujan mortar composition 1pc: 3PS, 1pc: 4Ps, and 1pc: 6 Ps age of 28 days, the mean value obtained Lumajang sand 307,20kg / cm², 257,60kg / cm² and 96.80 kg / cm², sand Lumajang and kelud of 338 , 40kg / cm², 124,80kg / cm², and 60,80kg / cm², and the use of sand kelud 212.00 kg / cm², 151.20 kg / cm², and 41.60 kg / cm². While the water absorption at 28 days average composition 1pc: 3pasir Lumajang by 1.29%, sand Lumajang and kelud of 1.85%, and sand kelud by 1.64%. Composition 1pc: 4 by 1.62% Lumajang sand, sand and sand kelud Lumajang by 3.44% and amounted to 3.15% kelud sand. KomPsisi 1pc: 6 amounted to 2.96% Lumajang sand, sand Lumajang and kelud by 4.68% and amounted to 5.49% kelud sand.